Flat out Fabulous: How Barbie's foot posture and occupations have changed over the decades, and the lessons we can learn. - Cylie Williams; Kristin Graham; Ian Griffiths; Suzanne Wakefield; Helen Banwell (PLoS ONE)
Objectives To explore the correlations/relationships between foot posture, equity and diversity, employment, and time in Barbie Land. Design A retrospective audit of the Barbie population (or their data from online catalogues) using a customised FEET system. That is Foot posture (flat or equinus); Equity (diversity and inclusion (EDI)); Employment (fashion vs employed); and Time period (decade of manufacture). Setting Barbie Land (Online Barbie catalogues of doll types). Participants 2750 Barbies and friends who lived in Barbie Land between 1959 to June 2024. Main outcome measures Over time there was a decreased prevalence in equinus foot posture from 100% in the first time period to 40% in the last. Barbie's flat foot posture had a very strong positive correlation with employment (r = 0.89, 95% Confidence Interval (95%CI) = 0.50 to 1.29), and time point (r = 0.85, 95%CI =  0.40 to 1.31), while equinus foot posture had a very strong positive correlation with fashion (r = 0.99, 95%CI = 0.87 to 1.11). Similarly, equity (diversity) had a very strong positive correlation with fashion (r = 0.98, 95%CI = 0.82 to 1.15), and strong positive correlation with employment (r = 0.79, 95%CI = 0.26 to 1.33). Conclusion Barbie's equinus foot posture is directly related to her high heel wearing. Barbie models her footwear choice based on task demands, being flat footed and wearing flat shoes when she needs to work on her feet, be physically active or more stable. Given Barbie is known to reflect societal norms, we contend this is most likely true for most high-heel wearers. While Barbie has moved with the times, it appears footwear health messaging about high heel wearing needs to catch up. Health professionals castigating high heels through public messaging, should remember that emphasising health benefits consistently drives positive behaviour change, over highlighting negative consequences. Barbie clearly makes sensible determinations regarding her body autonomy; high heel wearers should have that same ability.